2018
DOI: 10.1186/s12889-018-5665-5
|View full text |Cite
|
Sign up to set email alerts
|

The Young Women’s Health CoOp in Cape Town, South Africa: Study protocol for a cluster-randomised trial for adolescent women at risk for HIV

Abstract: BackgroundSouth Africa remains the global epicentre of HIV infection, and adolescent women have the highest incidence of HIV in the country. South Africa also has high rates of alcohol and other drug (AOD) use, violence, and gender inequality. Violence converges with AOD use, gender inequities and other disparities, such as poverty, to increase sexual risk and poor educational attainment for adolescent women. This study seeks to test the efficacy of peer recruitment and cofacilitation of the Young Women’s Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 28 publications
(9 reference statements)
0
20
0
Order By: Relevance
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our secondary search for studies that described the interventions identified, we found 27 additional manuscripts. Thus, the total number of manuscripts reviewed was 112 [19‐130]. These manuscripts described 74 unique intervention research studies (Table 1) […”
Section: Resultsmentioning
confidence: 99%
“…Both studies were conducted after 2010. We also assessed of the extent of youth engagement over time by comparing engagement in studies conducted in or before 2010 [19,20,22,23,25‐27,31,33,34,39‐41,45‐48,52‐54,59,60,66,68,72,73,77,78,80,82,83,88,89,109,115,121,130], to studies conducted after 2010 [21,24,28‐30,32,35‐37,42‐44,50,51,56‐58,60,62‐64,67,69‐71,75,76,79,81,84‐86,90,100,110,111,129]. We found youth engagement in 28 out of 37 interventions (76%) conducted in or before 2010, and in 30 out of 37 interventions (81%) conducted after 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have highlighted the health status of women in Africa, with emphasis on the major health challenges that they face such difficulties with access to maternal and reproductive health care services (Boerma et al 2008;Tapera 2018;Weschsberg et al 2018;Victora et al 2016;Fawole 2015; WHO 2015). They did not make any direct link between women's health and women empowerment in the African context.…”
Section: Introductionmentioning
confidence: 99%
“…Parental waiver has been requested to protect a participant’s confidentiality if they are uncomfortable having their mother consent for them. This approach has been used successfully in our previous South African studies with adolescents [ 19 , 51 ]. In loco parentis enables the participant to select a female adult (either identified by the participant themselves or by the study staff) to provide consent on her behalf.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment is conducted via street outreach at identified areas where AGYW are known to frequent. Street outreach is an established recruitment method that has been used successfully in previous research studies [50][51][52][53], including Tshwane WHC studies to reach and recruit a high number of women most at risk of HIV. Study staff visit these hotspots regularly to establish a known presence in the community and gain rapport with community members.…”
Section: Implementation Of Stigma and Discrimination Trainingmentioning
confidence: 99%